Impact of Powered Knee-Ankle Prosthesis on Low Back Muscle Mechanics in Transfemoral Amputees: A Case Series - Jayaraman, Chandrasekaran; Hoppe-Ludwig, Shenan; Deems-Dluhy, Susan; McGuire, Matt; Mummidisetty, Chaithanya; Siegal, Rachel; Naef, Aileen; Lawson, Brian E.; Goldfarb, Michael; Gordon, Keith E.; Jayaraman, Arun (Frontiers in Neuroscience, 2018)
Regular use of prostheses is critical for individuals with lower limb amputations to achieve everyday mobility, maintain physical and psychological health, and achieve a better quality of life. Use of prostheses is influenced by numerous factors, with prosthetic design playing a critical role in facilitating the extent of mobility capabilities an amputee could achieve. Thus, prostheses design can either lead to safe and efficient gait or biomechanically inefficient gait behavior. In addition to increased energy expenditure, such inefficient gait behavior could expose the prosthetic user to an increased risk of secondary musculoskeletal injuries and may eventually lead to rejection of the prosthesis. Consequently, researchers have exploited the technological advancements in various fields to improve prosthetic devices and customize them for user specific needs. One such prosthetic technology which has been continuously evolving over the past few decades, is the powered prosthetic device family. Presently, an active area of research is the design of novel controllers and components for these devices in order to enable the users of such powered devices to be able to reproduce gait biomechanics that is similar in biomechanical behavior to a healthy limb. In this case series, we studied the impact of using a powered knee-ankle prostheses (PKA) on two transfemoral amputees who currently use advanced microprocessor controlled knee prostheses (MPK). We integrated evaluations pertaining to kinematics, kinetics, metabolics, and functional activities of daily living to compare the efficacy between the MPK and PKA devices. Our case study investigations suggest that the PKA allows the participants to walk with gait kinematics similar to normal gait patterns observed in healthy limb. In addition to this it was also observed that using the PKA reduced the level of asymmetry in terms of mechanical loading and muscle activation specifically in the low back spinae regions and lower extremity muscles. Furthermore, the PKA allowed the participants to achieve a greater range of variable cadence than their predicate MPK, thus allowing them to safely ambulate in variable environments and also have the ability to dynamically control the lower limbs during mobility. Based on the results of this case study, it appears